Investigating the sequence-dependent mechanical properties of DNA nicks for applications in twisted DNA nanostructure design. Issue 1 (22nd November 2018) - Lee, Jae Young; Kim, Young-Joo; Lee, Chanseok; Lee, Jae Gyung; Yagyu, Hiromasa; Tabata, Osamu; Kim, Do-Nyun
Abstract: DNA nick can be used as a design motif in programming the shape and reconfigurable deformation of synthetic DNA nanostructures, but its mechanical properties have rarely been systematically characterized at the level of base sequences. Here, we investigated sequence-dependent mechanical properties of DNA nicks through molecular dynamics simulation for a comprehensive set of distinct DNA oligomers constructed using all possible base-pair steps with and without a nick. We found that torsional rigidity was reduced by 28–82% at the nick depending on its sequence and location although bending and stretching rigidities remained similar to those of regular base-pair steps. No significant effect of a nick on mechanically coupled deformation such as the twist-stretch coupling was observed. These results suggest that the primary structural role of nick is the relaxation of torsional constraint by backbones known to be responsible for relatively high torsional rigidity of DNA. Moreover, we experimentally demonstrated the usefulness of quantified nick properties in self-assembling DNA nanostructure design by constructing twisted DNA origami structures to show that sequence design of nicks successfully controls the twist angle of structures. Our study illustrates the importance as well as the opportunities of considering sequence-dependent properties in structural DNA nanotechnology.